Everyday things - Dorling Kindersley, Inc (New York : Dorling Kindersley, 1992)
Examines the inner workings of various devices and appliances found around the home, including the vacuum cleaner, flashlight, and washing machine
Keywords: Household appliances, Electric -- Juvenile literature; Household appliances, Electric; Machinery